Growth of Oyster Crassostrea Sp Settled on Shell and Stone Collectors - Fredinan Yulianda; Agus Soleh Atmadipura (Jurnal Moluska Indonesia, 2020)
During a 4-weeks period oyster spat at- tached on shell and stone collectors but not on roofing tile  submerged in estuarine and marine habitats. Collectors made of stone (rough surface) were better than collectors  of shell in terms of number of settled spat. The oyster spat settled at highest density on collectors close tothe sea.  The average growth in terms of weight was significantly different on the two types of collectors. The largest oysters  occurred on shell collectors near the river